Kemelayuan dan Batas-Batasnya Pada Masa Hindu-Buddha - Ery Soedewo (Balai Arkeologi Sumatera Utara, 2007)
AbstractBased on Chinese sources, at the first time Malay entity due to political entity. Spread of Ancient Malay language speaker to another place didn’t result lost identity on each participants. It’s also proved the ability of Malays in sea voyage, which is now to be one of their identity, besides Malay language itself.